The river king - Hoffman, Alice 1952- (Putnam's, 2000)
From the master storyteller, a suspenseful, lyrical account of one man's search for the truth behind an inexplicable death. For more than a century, the small town of Haddan, Massachusetts, has been divided, as if by a line drawn down the center of Main Street, separating those born and bred in the village from those who attend the prestigious Haddan School. But one October night the two worlds are thrust together due to an inexplicable death, and the town's divided history is revealed in all its complexity. The lives of everyone involved are unraveled: from Carlin Leander, the fifteen-year-old girl who is as loyal as she is proud, to Betsy Chase, a woman running from her own destiny; from August Pierce, a boy who unexpectedly finds courage in his darkest hour, to Abel Grey, the police officer who refuses to let unspeakable actions--both past and present--slide by without notice.
Keywords: Police -- Massachusetts -- Fiction; Preparatory school students -- Fiction; Massachusetts -- Fiction; Mystery fiction; Psychological fiction